Scalability analysis of LTE-EPC in an NFV environment (2018)
The scaling is a pivotal task to address workload variation that affects the performance of mobile networks. In the literature, several approaches propose scaling methods to the mobile Evolved Packet Core (EPC). However, so far, none of these approaches have exploited the benefits of elastic scaling to achieve an adaptive EPC in front of workload variations. In this work, we demonstrate that Network Functions Virtualization (NFV) allows incorporating elastic scaling to EPC aiming to address workload variations, and thus, to improve the network performance and the resources utilization. In particular, we present an elastic scaling mechanism in an NFV-based LTE-EPC, hereinafter, just called virtualized EPC (vEPC), a deployment of a vEPC that supports elastic scaling capability and a performance evaluation of each vEPC entity regarding throughput and latency. The evaluation results reveal a significant increase (~300%) in throughput and an important decrease (~70%) of latency when the vEPC uses our elastic scaling mechanism. These results corroborate the importance of including elastic scaling capability to improve the vEPC performance.